A Critical Analysis of Corporate Tax Planning Under the Nigeria Tax Act, 2025: Doctrinal, Judicial, and Comparative Perspectives - Adebayo, Bamidele Olasehinde (NIU Journal of Legal Studies, 2026)
The passing of the Nigeria Tax Act (NTA) 2025 marks a historic development in Nigeria’s tax regime with an overhaul of disparate and overlapping tax statutes into one cohesive framework that also incorporates many globally accepted anti-avoidance provisions. This paper critically examines the legal framework of corporate tax planning in Nigeria, distinguishing between acceptable tax avoidance and unacceptable tax evasion, while probing into the extent to which aggressive tax planning is restricted by the NTA 2025. Within the larger context of international tax governance, the paper explains how corporate tax planning methods have been restructured under the NTA 2025. It uses a doctrinal and comparative approach, incorporating ideas from the United States, the United Kingdom, and the Base Erosion and Profit Shifting (BEPS) programmes of the Organisation for Economic Cooperation and Development (OECD). The paper argues that Nigeria is transitioning from a permissive tax planning regime to a rules-based and substance-oriented system, inspired by Base Erosion and Profit Shifting (BEPS) principles, through doctrinal and comparative analysis with these countries and the OECD frameworks. The paper further contends that while the NTA 2025 contains measures to mitigate aggressive tax planning and promote transparency, the success of these provisions depends on the enforcement capacity and institutional coherence regarding corporate governance. Accordingly, the paper concludes that it is inevitable for corporate taxpayers to avoid aggressive tax planning and embrace sustainable tax compliance. Keywords: Corporate Tax Planning, Nigeria Tax Act 2025, Critical Analysis, Tax Avoidance, Tax Evasion.